2015
DOI: 10.1097/scs.0000000000001535
|View full text |Cite
|
Sign up to set email alerts
|

Failure Risk Estimates After Dental Implants Placement Associated With Plasma Rich in Growth Factor-Endoret in Osteoporotic Women Under Bisphosphonate Therapy

Abstract: There is disagreement as to whether it is safe to place implants in patients under bisphosphonates (BPs) therapy owing to the risk for developing BP-related osteonecrosis of the jaws (BRONJ). The American Association of Oral and Maxillofacial Surgeons recommends that dental implants should be avoided in oncologic patients treated with intravenous BPs. Conversely, for patients receiving oral BPs, dental implant placement is not explicitly contraindicated even if a cautious approach is suggested. The aim of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 49 publications
0
36
0
1
Order By: Relevance
“…Three other studies [15-17] did not find any significant differences for implantation success neither for osseointegration quality between osteoporotic and control groups. Holahan et al [16] found that osteoporosis did not show any correlation to local jaw bone quality, but when it was, set subjectively by surgeon, it highly correlated with implantation success (P < 0.01).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Three other studies [15-17] did not find any significant differences for implantation success neither for osseointegration quality between osteoporotic and control groups. Holahan et al [16] found that osteoporosis did not show any correlation to local jaw bone quality, but when it was, set subjectively by surgeon, it highly correlated with implantation success (P < 0.01).…”
Section: Resultsmentioning
confidence: 90%
“…In total 16 prospective studies [14,18,19,28,35-40,44,45,47,48,50,53] from which 5 were controlled clinical trials [38-40,44,48] and 1 cross-sectional study [45], 23 retrospective studies [15-17,20,23-27,29-34,41-43,46,49,51,52,54] and two case series studies [21,22] were included in present research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 Literatüre göre, oral bifosfonat kullanan hastalarda dental implant cerrahisi ile ilişkili bifosfanat kullanımına bağlı çenelerin osteonekrozu (BRONJ) gelişme riski düşüktür. 16,25,26 Diz ve ark. tarafından yapılan bir derlemede, dental implant uygulamasını takiben BRONJ gelişen hastaların 11'inin oral 16' sının ise intravenöz olarak bifosfanat kullanmakta olduğu, ayrıca implant uygulaması ve BRONJ gelişimi arasında ortalama 16 ay olduğu belirtilmiştir.…”
Section: Discussionunclassified